2021
DOI: 10.1038/s41467-021-27070-5
|View full text |Cite
|
Sign up to set email alerts
|

Independent control of mean and noise by convolution of gene expression distributions

Abstract: Gene expression noise can reduce cellular fitness or facilitate processes such as alternative metabolism, antibiotic resistance, and differentiation. Unfortunately, efforts to study the impacts of noise have been hampered by a scaling relationship between noise and expression level from individual promoters. Here, we use theory to demonstrate that mean and noise can be controlled independently by expressing two copies of a gene from separate inducible promoters in the same cell. We engineer low and high noise … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…Reference [119] first showed that the stationary mean and variance of the controlled species could be independently assigned within their admissibility region by considering two independent control inputs. Experiments reported by by Gerhardt et al [122] also led to the same conclusions, albeit using a different approach. This result needs to be contrasted with in-vivo control where it is possible to act on the mean and the variance of the controlled species independently but using one single control input [113,105].…”
Section: Centralized Population and Single-cell Controlsupporting
confidence: 63%
“…Reference [119] first showed that the stationary mean and variance of the controlled species could be independently assigned within their admissibility region by considering two independent control inputs. Experiments reported by by Gerhardt et al [122] also led to the same conclusions, albeit using a different approach. This result needs to be contrasted with in-vivo control where it is possible to act on the mean and the variance of the controlled species independently but using one single control input [113,105].…”
Section: Centralized Population and Single-cell Controlsupporting
confidence: 63%
“…Therefore, it is necessary to understand the origin of the noise, as well as control noise rationally for various applications. Regarding noise regulation, various strategies have been proposed to control gene expression noise independently, including engineering transcription and translation in synthetic gene circuits ( 61 , 62 ), introducing pulsatile input to control the promoter activation frequency and transcription rate independently ( 63 ) and expressing two copies of the target gene from separate circuits with different characteristics ( 64 ), among others. Through dSort-Seq profiling of different combinations of promoters and RBSs in E. coli , the transcriptional effect on gene expression noise was revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to understand the origin of the noise, as well as control noise rationally for various applications. Regarding noise regulation, various strategies have been proposed to control gene expression noise independently, including engineering transcription and translation in synthetic gene circuits 58,59 , introducing pulsatile input to control the promoter activation frequency and transcription rate independently 60 and expressing two copies of the target gene from separate circuits with different characteristics 61 , among others. Through dSort-Seq profiling of different combinations of promoters and RBSs in E. coli , the transcriptional effect on gene expression noise was revealed.…”
Section: Discussionmentioning
confidence: 99%